2010
DOI: 10.1152/ajplung.00216.2009
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibition of arginase attenuated airway allergic reactions and inflammation in a Dermatophagoides farinae-induced NC/Nga mouse model

Abstract: The expression of arginase I has been a focus of research into the pathogenesis of experimental asthma, because arginase deprives nitric oxide synthase (NOS) of arginine and therefore participates in the attenuation of bronchodilators such as nitric oxide (NO). The present study used an intranasal mite-induced NC/Nga mouse model of asthma to investigate the contribution of arginase to the asthma pathogenesis, using an arginase inhibitor, N -hydroxy-nor-L-arginine (nor-NOHA). The treatment with nor-NOHA inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 48 publications
4
49
0
Order By: Relevance
“…The expression of arginase is strongly induced by Th2 cytokines, including IL-13 [35]; ABH markedly attenuated the allergen-induced increase in IL-13 in our model, indicating that the increased arginase activity and the inhibitory effect of ABH thereon may result from changes in IL-13. This is consistent with a recent finding in a mouse model of acute asthma, showing that intranasal application of the arginase inhibitor N v -hydroxy-nor-arginine (nor-NOHA) prevents house dust mite-induced increases in Th2 cytokine expression and arginase activity in the lung [38]. It is tempting to speculate that the previously observed anti-allergic effect of inhaled ABH [19] underlies the reduction of Th2 cytokine release and subsequent arginase induction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The expression of arginase is strongly induced by Th2 cytokines, including IL-13 [35]; ABH markedly attenuated the allergen-induced increase in IL-13 in our model, indicating that the increased arginase activity and the inhibitory effect of ABH thereon may result from changes in IL-13. This is consistent with a recent finding in a mouse model of acute asthma, showing that intranasal application of the arginase inhibitor N v -hydroxy-nor-arginine (nor-NOHA) prevents house dust mite-induced increases in Th2 cytokine expression and arginase activity in the lung [38]. It is tempting to speculate that the previously observed anti-allergic effect of inhaled ABH [19] underlies the reduction of Th2 cytokine release and subsequent arginase induction.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, allergeninduced inflammatory responses are attenuated in mice that overexpress endothelial NOS [49] and are elevated in iNOS -/-mice [50] compared with wild-type mice. Consistent with our observations, treatment with the arginase inhibitor nor-NOHA reduced inflammatory cell numbers in the bronchoalveolar lavage (BAL) of allergen-challenged mice [38,50]. However, the arginase inhibitor S-(2-boronoethyl)-L-cysteine did not affect inflammatory cell numbers or cytokine levels in BAL, and even further enhanced peribronchiolar and perivascular inflammation in another mouse model of acute allergic asthma [51].…”
Section: Discussionsupporting
confidence: 86%
“…This results in decreased production of bronchodilatory NO as well as increased synthesis of proinflammatory and procontractile peroxynitrite, which contribute to the development of allergen-induced airway hyperresponsiveness (Meurs et al, 2002;Maarsingh et al, 2006Maarsingh et al, , 2009a. Treatment with inhaled arginase inhibitors protected against allergeninduced airway obstruction, airway hyper-responsiveness, and airway inflammation in guinea pig (Maarsingh et al, 2008b) and mouse (North et al, 2009;Takahashi et al, 2010) models of acute allergic asthma. Using repeatedly allergen-challenged guinea pigs, we recently demonstrated that increased arginase activity also has a major role in airway remodeling in chronic asthma, as indicated by effective inhibition of these features by inhalation of the specific (Baggio et al, 1999) arginase inhibitor 2(S)-amino-6-boronohexanoic acid (ABH) .…”
Section: Introductionmentioning
confidence: 99%
“…In mouse models of asthma, arginase-1 mediated allergic inflammatory response in lung epithelial cells through the modulation of NFκB signaling pathway (120,121). Furthermore, treatment with arginase specific inhibitor, 2(S)-amino-6-boronohexonic acid (ABH), significantly ameliorated pulmonary inflammation and airway fibrosis in guinea pigs repeatedly exposed to LPS.…”
Section: Arginase Derived-monocytes/macrophages-an Inducer Of Acute Imentioning
confidence: 99%
“…In line with these findings, arginase-1 produced by macrophages has been shown to be responsible for the pathophysiology of asthma which is a complex disease manifested by allergic airway inflammation and airway hyperreactivity. In mouse models of asthma, arginase-1 drives allergic inflammatory response in lung epithelial cells through the modulation of NFκB signaling pathway (120,121). Furthermore, treatment with an arginase specific inhibitor, ABH, significantly ameliorated pulmonary inflammation and airway fibrosis in guinea pigs repeatedly exposed to LPS.…”
Section: Hpv16e7-induced Cutaneous Hyperinflammation To Dncb Is Assomentioning
confidence: 99%